Palladian Gold: Chemical Composition, Minerals in Association, and Physicochemical Conditions of Formation at Different Types of Gold Deposits - Galina A. Palyanova; Pavel S. Zhegunov; Tatiana V. Beliaeva; Valery V. Murzin; Andrey A. Borovikov; Nikolay A. Goryachev (Minerals, 2023)
This paper reviews and summarizes the available information on the composition of palladian gold with various contents and sets of isomorphic impurities (Ag, Cu, Hg) at 50 deposits and ore occurrences with Au-Pd mineralization. It is revealed that Palladian gold is represented by the systems Au–Pd, Au–Pd–Hg, Au–Pd–Cu, and Au–Pd–Ag–Hg, but more frequently corresponds to Au–Pd–Ag, Au–Pd–Ag–Cu, and Au–Pd–Ag–Cu–Hg. Objects with palladian gold belong to different types of gold deposits and to the deposits at which the main components of ores are PGE, Cr, Cu, Ni, V, and Ti. We propose a classification of the types of deposits with palladian gold: (1) PGE ore deposits related to mafic–ultramafic magmatic complexes (two subtypes—(a) low-sulfide-grade (less than 2%–5% sulfides) Alaskan, and (b) high-sulfide-grade (more than 5% sulfides) Norilsk); (2) orogenic gold deposits (OG); (3) epithermal (porphyry) gold–copper deposits (EPGC); (4) iron oxide copper gold deposits (IOCG); (5) ferruginous quartzite deposits; (6) volcanic exhalation; and (7) gold-PGE placers of five subtypes corresponding to the types of 1–5 primary sources. Palladian gold is mainly high-fineness (910‰–990‰), is less frequently medium-fineness, and contains Ag and Cu, but does not contain Hg at the deposits of types 1, 3, and 4. The only exception is the Au-Pd-Hg Itchayvayam ore occurrence (Kamchatka, Russia), for which two varieties of Pd,Hg-bearing native gold (fineness 816‰–960‰ and 580‰–660‰) are determined. Low-fineness palladian gold with the major content of Ag is typical of OGD deposits. Medium-fineness palladian gold occurs at ferruginous quartzite deposits and in volcanic exhalations. Hg, Ag, Cu-bearing high-fineness palladian gold is present mainly in placer deposits (type 7). The most common minerals in association with palladian gold are arsenides, stibioarsenides, sulfides, stannides, bismuthides, tellurides, and selenides of Pd and Pt. These are typical of deposit types 1 and 7. The minerals of Au, Ag, and Cu (tetra-auricupride, ...